NEW POSSIBILITIES OF THE METHOD OF FROSTING AT IRONS CASTING - A. M. Bodjako; S. V. Galagaev; A. A. Bodyako; A. A. Suponev (Литьë и металлургия)
Efficiency of use of plugs from grey and high-strength cast irons, received by a «Freezing-uр» technology of continuous- iterative casting, as sliding friction bearings in the various hard loaded knots is shown